Pengembangan Sistem Pengarsipan Surat Di Bidang Sumber Daya Manusia dan Komunikasi Hukum Administrasi (SDM & KHA) Pada PT PLN (Persero) Wilayah Lampung - Kurnia Muludi; Anie Rose Irawati; Eva Diana Sari (Jurusan Ilmu Komputer Fakultas MIPA Universitas Lampung, 2015)
AbstractAs the development of technologies in computers, human beings are competing to create the newest technology in the form of hardware and software. The big companies are certainly use computer-based information system (CBIS) for example PT PLN (Persero) of Lampung Region. PT PLN (Persero) of Lampung Region is a company that supplies electricity for Lampung Province. They have activities that associated with mailing and receiving letter. The received letters are accommodated in the secretary and are documented and archived using computer in semi manual manner. The computer system used less efficient and with given amount of letters often cause mistakes and slowness in registering them. This caused the slowness of searching of the archives and as well in generating and recap for the letters reporting. Moreover the letters documentation security is absent. Because of that, the existing system needs to be developed to improve services and good security. This research goal is to make a system for a letters documentation that has security features such as logins, and a good encryption and decryption using Twofish algorithms. This research used Visual basic 6.0 programming language combined with MySQL database and Crystal Report. The system development methodology used in this research is Waterfall. Black Box testing results show that the letter archive system has been successfully developed in accordance with the needs of the user. Key words: Algorithm Twofish, Crystal Report, Hardware, MySQL, Black Box Testing, Software, Mail Archiving System, Visual Basic